2004
DOI: 10.1111/j.1475-097x.2004.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial velocities measured during adenosine, dobutamine and supine bicycle exercise: a tissue Doppler study in healthy volunteers

Abstract: ASE evokes significantly less LV systolic response compared with both DSE and ESE. Increased velocity (P<0.05 versus rest) and strain (P>0.05) response at a much lower HR indicates that adenosine has minor effects on contraction presumably secondary to vasodilatation. Powerful chronotropic response to DSE and ESE is probably prerequisite for strong velocity response at the expense of strain and displacement. TVI-assisted stress echocardiography thereby shows different LV systolic response in healthy individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…The atrial contraction is an active process, determined by the muscle strength in the atrium and is therefore less influenced by passive forces in the blood. Both PSV and A’ showed a significant increase with heart rate during the two different stress tests (Figs 2 and 4), which confirms the results from other studies (Saha et al. , 2004; Jassal et al.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The atrial contraction is an active process, determined by the muscle strength in the atrium and is therefore less influenced by passive forces in the blood. Both PSV and A’ showed a significant increase with heart rate during the two different stress tests (Figs 2 and 4), which confirms the results from other studies (Saha et al. , 2004; Jassal et al.…”
Section: Discussionsupporting
confidence: 90%
“…, 2005). These results were partly confirmed by another study reporting increased longitudinal motion of the left ventricular myocardium during physical exercise (Saha et al. , 2004).…”
Section: Introductionsupporting
confidence: 72%
“…We found that the peak velocity of systolic LV contraction was higher in the endurance athletes during exercise of moderate-to-maximal intensity, but not at rest. The highest PSV values (i.e., in the EG group during performance at VO 2max ) observed here are among the highest reported to date (Støylen et al 2003;Saha et al 2004;Bjällmark et al 2009). Furthermore, endurance athletes demonstrated an increase in PSV during exercise.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, myocardial deformation or strain, which more directly reflects local myocardial function, is preferable for measurement [16,17]. In our study, in the normally perfused myocardium, strain and SR did not change with adenosine stress, since adenosine has no direct inotropic influence on normal myocardium, although it has an obvious vasodilative function [18].…”
Section: Adenosine Stress Echocardiographymentioning
confidence: 95%